2014
DOI: 10.1111/j.1948-7134.2014.12071.x
|View full text |Cite
|
Sign up to set email alerts
|

Triatominae in furnariid nests of the Argentine Gran Chaco

Abstract: Triatomines (Hemiptera, Reduviidae) are bloodsucking insects involved in the transmission of Trypanosoma cruzi, the causative agent of Chagas disease, an important public health problem in Latin America. The triatomine species found in sylvatic habitats generally play a limited epidemiological role compared to domestic species, but they may act as a reinfestation source of dwellings after insecticide spraying and have to be carefully considered in control strategies of Chagas disease transmission. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
9
0
9
Order By: Relevance
“…According to Marti et al . [ 37 ], several triatomine species cohabit in the same microhabitat (e.g. Ps.…”
Section: Discussionmentioning
confidence: 99%
“…According to Marti et al . [ 37 ], several triatomine species cohabit in the same microhabitat (e.g. Ps.…”
Section: Discussionmentioning
confidence: 99%
“…has not been reported, experimental studies have shown that P. coreodes and P. tertius might become infected with T. cruzi (1) (38) . Additionally, sylvatic Triatoma platensis inhabiting the nests of Phacellodomus sibilatrix were found to be naturally infected by T. cruzi in a typical area of the Chaco region of Argentina (39) . Given that natural infection by T. cruzi in free-living small mammals is well documented in the Pantanal region (13) (16) (40) , the presence of O. mamorae in thornbird nests might constitute a risk factor for P. coreodes infection by T. cruzi.…”
Section: Identifi Cation Of Trypanosoma Cruzimentioning
confidence: 99%
“…platensis incrementarían la adecuabilidad climática, pasando desde un nivel medio a alto, en sus distribuciones australes llegando a ocupar provincias en las cuales no están presentes en la actualidad. Estas especies poseen una baja importancia epidemiológica, siendo encontradas esporádicamente infectadas con T. cruzi (Marti et al, 2014, Galvão y Justi, 2015 Argentina. Estos resultados concuerdan con los obtenidos a partir del modelo 8.5, donde si bien se reduciría la adecuabilidad climática en la región este, esta se incrementaría hacia la zona de los Valles Calchaquíes.…”
Section: Discussionunclassified
“…Triatoma infestans, es una especie que habita casi exclusivamente el domicilio o peridomicilio debido a su especialización evolutiva en la estabilidad del hábitat (Lauricella et al, 2005, Galvao y Justi, 2015. Sin embargo, en los últimos años se han citado poblaciones silvestres en Argentina, Bolivia, Chile y Paraguay (Noireau et al, 2000, Ceballos et al, 2009, Bacigalupo et al, 2010, Buitrago et al, 2010, Ceballos et al, 2011, Rolón et al, 2011, Waleckx et al, 2012, Marti et al, 2014. Estos focos silvestres abren nuevos interrogantes, debido a que a pesar de existir resultados concretos en varios estudios es difícil afirmar si la reinfestación de los domicilios/peridomicilios tratados con insecticidas se debe a subpoblaciones residuales y/o resistentes o a la colonización desde los focos silvestres (Cecere et al, 2004, Dujardin et al, 2007, Vazquez-Prokopec et al, 2009, Ceballos et al, 2011.…”
Section: Antecedentesunclassified
See 1 more Smart Citation